1994
DOI: 10.1172/jci117530
|View full text |Cite
|
Sign up to set email alerts
|

Diminished virulence of a sar-/agr- mutant of Staphylococcus aureus in the rabbit model of endocarditis.

Abstract: Microbial pathogenicity in Staphylococcus aureus is a complex process involving a number of virulence genes that are regulated by global regulatory systems including sar and agr. To evaluate the roles of these two loci in virulence, we constructed sar-lagr-mutants of strains RN6390 and RN450 and compared their phenotypic profiles to the corresponding single sar-and agr-mutants and parents. The secretion of all hemolysins was absent in the sar-lagr-mutants while residual 8-hemolysin activity remained in single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
274
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(286 citation statements)
references
References 36 publications
10
274
1
Order By: Relevance
“…S. aureus RN6390, 67 isogenic mutant of RN6390, ALC135 (agr::tetM, sar::Tn917/LTV1) 69 (generously provided by Ambrose Cheung, Dartmouth Medical School, Hanover, NH), and Lactococcus lactis strain MG1363 (generously provided by Todd R. Klaenhammer, North Carolina State University, Raleigh, NC) were used in this study, and routinely cultured in brain heart infusion (BHI) broth (BD San Jose, CA) broth at 37°C. For challenge experiments, overnight cultures were diluted 1:50 into 25 ml of pre-warmed BHI broth and grown at S. aureus clinical isolate expressing toxic shock syndrome toxin-1 (TSST-1).…”
Section: Methodsmentioning
confidence: 99%
“…S. aureus RN6390, 67 isogenic mutant of RN6390, ALC135 (agr::tetM, sar::Tn917/LTV1) 69 (generously provided by Ambrose Cheung, Dartmouth Medical School, Hanover, NH), and Lactococcus lactis strain MG1363 (generously provided by Todd R. Klaenhammer, North Carolina State University, Raleigh, NC) were used in this study, and routinely cultured in brain heart infusion (BHI) broth (BD San Jose, CA) broth at 37°C. For challenge experiments, overnight cultures were diluted 1:50 into 25 ml of pre-warmed BHI broth and grown at S. aureus clinical isolate expressing toxic shock syndrome toxin-1 (TSST-1).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have found that agr is required for virulence in models of septic arthritis, osteomyelitis, endophthalmitis and pulmonary infections (Abdelnour et al, 1993;Booth et al, 1997;Gillaspy et al, 1995;Heyer et al, 2002). However, other evidence seems to question the role of the agr system in virulence in other models (Cheung et al, 1994;Kielian et al, 2001). In cystic fibrosis (CF) patients with S. aureus infections, the agr system was inactive, suggesting that agr activation may not be necessary for infection (Goerke et al, 2000).…”
Section: Quorum Sensing In Staphylococcus Aureus Virulencementioning
confidence: 99%
“…1). Interestingly, the pathogenicity of S. aureus strains lacking either agr or sar is reduced significantly, and those strains that lack both the agr and the sar loci are almost completely attenuated (1,10,39).In this paper, we report the purification of the S. aureus SigB protein, designated SB , and promoter-specific transcription by the core RNAP reconstituted with SB . Transcriptional analysis of the sar operon by the core RNAP reconstituted with SB provides the first clue as to how the biosynthesis of some of the toxins can be modulated in response to various physiological and environmental stress conditions.…”
mentioning
confidence: 99%
“…1). Interestingly, the pathogenicity of S. aureus strains lacking either agr or sar is reduced significantly, and those strains that lack both the agr and the sar loci are almost completely attenuated (1,10,39).…”
mentioning
confidence: 99%